Curriculum Management Quality in Vocational High Schools: Planning, Organizing, Implementation, and Evaluation - Almes Gangga; Wirda Yetti; Rijal Abdullah; Refdinal Refdinal (Juwara: Jurnal Wawasan dan Aksara, 2026)
Curriculum management quality is a fundamental determinant of educational effectiveness in vocational high schools (SMK). This study assesses curriculum management quality across four dimensions: curriculum planning (D1), curriculum organizing (D2), curriculum implementation (D3), and curriculum evaluation (D4), from the perspectives of school administrators and teachers. A quantitative survey design was employed involving 145 respondents selected through proportionate stratified random sampling across five SMK in West Sumatra, Indonesia. Data were collected using a validated questionnaire (44 items; Cronbach's alpha = 0.91) and analyzed using descriptive statistics and one-way ANOVA. Results indicate that overall curriculum management quality achieved a mean score of 3.69 out of 5.00 (Good category). Curriculum Planning (D1) achieved the highest mean (M = 3.82), while Curriculum Evaluation (D4) was the most critical dimension (M = 3.58). Significant differences in perceptions were found across respondent positions (F = 4.83, p = 0.003). This study contributes an integrated four-dimension quantitative framework for assessing curriculum management quality in SMK, providing empirical evidence that evaluation functions represent the weakest link in the curriculum management cycle and that multi-stakeholder data collection is essential for accurate institutional quality monitoring.